Distribution of the Antarctic Sea-birds in the Outer Margin of the Summer Pack Ice Area - Yasuhiko NAITO; Keiji NASU; Hiroshi SUZUKI (Antarctic Record, 1979)
The distribution of the Antarctic sea-birds was investigated in 1976-1977 and 1977-1978 summer seasons. The observations were performed along the outer margin of the pack ice area between longitude 50° E and 165° E. The investigated area was centered latitudinally between 62° S and 68° S. Twelve species observed in this area are divided into two groups, namely, rare species group and dominant species group. The species which rarely appeared, such as light-mantled sooty albatross, Antarctic petrel, sooty albatross, wandering albatross and Antarctic skua, are not krill-feeders. The latter group is composed of sooty shearwater, Wilson's storm petrel, snow petrel, Antarctic prion, giant petrel, cape pigeon and Antarctic petrel. These species showed the circumpolar distribution, and they are known to feed on the krill, except sooty shearwater. The relation between the sea-bird distribution and the krill was suggested.